Green laser diodes with low operation voltage obtained by suppressing carbon impurity in AlGaN: Mg cladding layer. Issue 5 (22nd December 2015) - Tian, Aiqin; Liu, Jianping; Zhang, Liqun; Ikeda, Masao; Zhang, Shuming; Li, Deyao; Fan, Xiaowang; Zhou, Kun; Wen, Pengyan; Zhang, Feng; Yang, Hui
Abstract: Electrical properties of Al0.07 Ga0.93 N: Mg samples with different carbon impurity concentrations were investigated by Hall measurements. By reducing carbon impurity concentration from 2×10 18 cm ‐3 to 5×10 16 cm ‐3, the resistivity of p‐Al0.07 Ga0.93 N decreases from 7.4 Ω·cm to 2.2 Ω·cm. By applying the growth conditions of low‐temperature AlGaN: Mg with low carbon incorporation to cladding layer of green LD structure, we have obtained green LDs with series resistance as low as 2.4 Ω and operation voltage of 4.9 V at 4 kA/cm 2 . The green LDs lased at 508 nm with a threshold current density of 8.5 kA/cm 2 and a slope efficiency of 0.22 W/A. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)